Differences in Productivity of Student Questions in Online and Offline Learning in Post-Pandemic E-Learning State Islamic Religious Institute Ponorogo Regency - Nurul Malikah (STAI Hubbulwathan Duri, 2023)
The pandemic period provides free communication space through cyberspace, including students expressing their abilities by submitting questions during lectures through e-learning applications. When students study online with various daily behaviors that are carried out, they are still connected to online lecture activities. Concentration, learning behaviors, communication, virtual world literacy delivered, and interactions with other students or lecturers seem semi-formal. Several research facts about the ability to interact in language and collaborate which are supported by good learning processes and strategies will and good student behavior and good attitudes during online learning so that the level of saturation is minimal, it is suspected that students have progressed in the number of asking questions through e-learning. This data will be explored through a questionnaire from IAIN PONOROGO students who use e-learning during online learning. The questionnaire was conducted for students doing offline learning. Different test analyses to see the difference in the productivity of online and offline learning questions. The results show that the difference in question productivity is more significant in online learning. Further research is suggested to discuss the relevance of the questions between the themes discussed and the uniqueness of the field facts.